Facile synthesis of anion conductive poly(2, 6-dimethyl-1, 4-phenylene oxide)s from a clickable di-quaternized side-chain precursor. (20th May 2019) - Zhu, Zhengfang; Cui, Peng; Lu, Yu; Wu, Jianrong; Zeng, Jing; Ma, Weiye; Zhao, Xinsheng; Zhu, Yuanqin
Abstract: To develop a facile route towards anion conductive polymers containing multi-cation side chains, novel anion conductive poly (2, 6-dimethylphenylene oxide)s (DQPPO-x-I) was prepared from a clickable di-quaternized side-chain precursor, via Cu(I)-catalyzed azide-alkyne click chemistry. The new precursor was synthesized from commercially available 2-{[2-(dimethylamino)ethyl]methylamino}ethanol and 3-bromopropyne via nucleophilic substitution and Menshutkin reaction. The chemical structures of the precursor and DQPPO-x-I polymers were characterized by 1 H NMR and FT-IR. Small angle X-ray scattering and transmission electron microscopy revealed that the obvious micro-phase separation was formed in the DQPPO-x-I membranes. The optimized DQPPO-19-OH membrane with ion exchange capacity of 2.13 meq./g exhibited the highest hydroxide conductivity of 31.6 mS/cm at 80 °C, tensile strength of 64 MPa, and thermal stability (onset decomposition temperature up to 187 °C). Graphical abstract: Image 1 Highlights: A clickable di-quaternized side-chain precursor was successfully synthesized. Novel AEMs were successfully prepared from the new precursor via click chemistry. A facile route towards AEMs containing multi-cation side chains was developed.